Analisis Kualitas Pelayanan, Harga dan Efisiensi Waktu Terhadap Kepuasan Pelanggan Pada Usaha Jahit - Lestari, Devi Puji; Mu’awwanah, Uliyatul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
With the emergence of various e-commerce in online media, making people choosy in terms of service quality, price and time. This makes the sewing service business improve service quality, set affordable prices and complete orders on time so that customers do not change places. This study was conducted to determine how much service quality, price, and timeliness affect customer satisfaction in the sewing business “Caca Curtains, Convection, and Vermak”. This study uses a quantitative method with a survey approach with sampling using accidental sampling techniques. Data collection was carried out through a questionnaire distributed to 78 respondents and processed using SPSS ver25 which was analyzed by multiple linear regression statistical methods. The results of the analysis state that individually service quality, price and time efficiency have a significant influence on customer satisfaction with the t value obtained by each variable greater than the t table (1.665) and has a significance value of 0.000. Simultaneously, service quality, price and time efficiency have a positive influence on customer satisfaction with the obtained f value of each variable is 251,650 with a significance value of 0.000. These results state that winning the hearts of customers is one of the important keys to the success of a business.